2022
DOI: 10.3847/1538-4357/ac7ce7
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution M-band Spectroscopy of CO toward the Massive Young Stellar Binary W3 IRS 5

Abstract: We present in this paper the results of high spectral resolution (R = 88,100) spectroscopy at 4.7 μm with iSHELL/IRTF of hot molecular gas close to the massive binary protostar W3 IRS 5. The binary was spatially resolved, and the spectra of the two sources (MIR1 and MIR2) were obtained simultaneously for the first time. Hundreds of 12CO ν = 0–1, ν = 1–2 lines, and ν = 0–1 transitions of the isotopes of 12CO were detected in absorption and are blueshifted compared to the cloud velocity v LSR =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(33 citation statements)
references
References 72 publications
0
33
0
Order By: Relevance
“…Previous studies of the MIR water absorption spectrum toward massive protostars have revealed a rich spectral content. High spectral resolution observations can provide much insight into the characteristics of these regions (e.g., Knez et al 2009;Indriolo et al 2015;Barr et al 2018;Dungee et al 2018;Indriolo et al 2018;Rangwala et al 2018;Goto et al 2019;Barr et al 2020;Indriolo et al 2020;Nickerson et al 2021;Barr et al 2022aBarr et al , 2022bLi et al 2022;Nickerson et al 2023). Water has also been studied at high spectral resolution via pure rotational transitions, using the heterodyne instruments on board SWAS, Odin, and Herschel Space Observatory (e.g., Snell et al 2000;Wilson et al 2003;Chavarría et al 2010;Karska et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies of the MIR water absorption spectrum toward massive protostars have revealed a rich spectral content. High spectral resolution observations can provide much insight into the characteristics of these regions (e.g., Knez et al 2009;Indriolo et al 2015;Barr et al 2018;Dungee et al 2018;Indriolo et al 2018;Rangwala et al 2018;Goto et al 2019;Barr et al 2020;Indriolo et al 2020;Nickerson et al 2021;Barr et al 2022aBarr et al , 2022bLi et al 2022;Nickerson et al 2023). Water has also been studied at high spectral resolution via pure rotational transitions, using the heterodyne instruments on board SWAS, Odin, and Herschel Space Observatory (e.g., Snell et al 2000;Wilson et al 2003;Chavarría et al 2010;Karska et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Millimeter studies reveal complex structures surrounding the binary on a large scale (10 3 -10 5 au), including a hot molecular core with outflows, jet lobes, shocks, and a circumbinary toroid (Imai et al 2000;Rodón et al 2008;Wang et al 2012Wang et al , 2013Purser et al 2021). In the infrared M-band (4.7 μm), high spectral resolution (R = 88,100) observations of rovibrational transitions of CO and its isotopologues (Li et al 2022) show various absorbing structures along the pencil beam line of weight against the pencil beam MIR background. Physical conditions such as temperature and column density have been derived from these CO observations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations